2022
DOI: 10.3389/fphar.2022.759742
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Fetal Immunity: A Systematic Review and Meta-Analysis of the Association Between Antenatal Corticosteroids and Retinopathy of Prematurity

Abstract: Background: Retinopathy of prematurity (ROP) is a major cause of childhood blindness. Antenatal corticosteroids (ACS) exposure is known to ameliorate the risk of and mortality of neonatal morbidities. However, the effect of ACS on ROP development is currently unknown. We conducted a meta-analysis with up-to-date evidence to assess the association between ACS exposure and the development of ROP in at-risk preterm infants.Methods: PubMed, EMBASE, Scopus, Web of Science, and the Cochrane Library were systematical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…Our study found that ACS was associated with a decreased incidence of severe ROP in NICU infants born to mothers with both clinical and histological chorioamnionitis. Recently, a meta-analysis showed the association between ACS exposure and the development of ROP in preterm infants, including 63 cohort studies involving infants born at gestational ages from 25 to 32 weeks [ 26 ]. The results showed ACS exposure was associated with significantly lower odds of ROP progression (aOR 0.48, 95% CI 0.26–0.89).…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that ACS was associated with a decreased incidence of severe ROP in NICU infants born to mothers with both clinical and histological chorioamnionitis. Recently, a meta-analysis showed the association between ACS exposure and the development of ROP in preterm infants, including 63 cohort studies involving infants born at gestational ages from 25 to 32 weeks [ 26 ]. The results showed ACS exposure was associated with significantly lower odds of ROP progression (aOR 0.48, 95% CI 0.26–0.89).…”
Section: Discussionmentioning
confidence: 99%
“…Postnatal systemic glucocorticoids reduce the incidence of severe ROP in some but not all studies [25,26]. Meta-analysis of 196,264 infants from 63 studies (Pubmed search: "steroid*", "cortico*", "betamethasone", "dexamethasone") shows that antenatal corticosteroid exposure may decrease ROP severity but not prevent ROP [27]. In a large cohort study of 1,472 neonates with birth weight < 500 g, postnatal steroid exposure is associated with a higher risk of ROP.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that infants born extremely preterm and with very low birth weight have a decreased risk of severe ROP after ACS [31,32]. However, a recent meta-analysis suggests that ACS treatment may decrease, but not prevent, the severity of ROP [33]. At present, the evidence of the effect of ACS on ROP is based on some retrospective studies, and more rigorously designed RCT experiments are needed to improve the level of evidence.…”
Section: Plos Onementioning
confidence: 99%